Exome sequencing and RNA analysis identify two novel CPLANE1 variants causing Joubert syndrome. Issue 3 (29th January 2022) - Fei, Hongjun; Wu, Yi; Wang, Yanlin; Zhang, Junyu
Abstract: Background: Joubert syndrome (JS) is a genetically heterogeneous disorder; its genetic etiology involves more than 35 genes, and a limited number of studies have investigated the pathogenic mechanism of variants in patients with JS. RNA splicing analysis is critical to determine the functional significance for noncanonical splicing variants. Methods: Whole exome sequencing was performed to screen the causative gene variants in a JS family. Sanger sequencing was used to verify the variants. cDNA PCR products were analyzed and functional experiments were performed to determine the pathogenicity of the variants. Results: The clinical phenotypes and CPLANE1 variants in the JS patient were analyzed and proved consistent. We identified two novel heterozygous variants of CPLANE1 in the proband first, including c.4459del (frameshift variant) and c.7534‐14G > A (intronic variant). We analyzed the pathogenic consequences of the 2 variants and classified the c.4459del as likely pathogenic according to the ACMG/AMP guidelines; however, the pathogenic significance of c.7534‐14G > A was uncertain. Furthermore, we performed RNA splicing analysis and revealed that the noncanonical splicing variant (c.7534‐14G > A) caused aberrant exon 37 skipping. It produced an aberrant transcript that was predicted to encode a C‐terminal truncated protein. Conclusions: The genetic variation spectrum of JS caused by CPLANE1 was updated. Two novel variants further deepened our insight into the disease's molecular mechanism and confirmed the significance of diagnostic whole‐exome sequencing. Abstract : The genetic variation spectrum of JS caused by CPLANE1 was updated. Two novel variants further deepened our insight of the disease's molecular mechanism and confirmed the significance of diagnostic whole exome sequencing.